OPA: An AI System for Automating the Correction and Analysis of Portuguese Dictations - Bueno, Erika C. Matesz; Finamor, Polyana Graf; Cardoso, Thaynara; Garcia, Ana Cristina Bicharra (Anais do Simpósio Brasileiro de Sistemas Colaborativos (SBSC); 2025: Anais do XX Simpósio Brasileiro de Sistemas ColaborativosDO - 10.5753/sbsc.2025.6639, 2025)
This paper presents an OPA (Observation, Processing, and Assistance) proof of concept, an AI-based system designed to support Portuguese language teachers in public schools by automating the correction and analysis of handwritten dictations. OPA uses OCR technologies and natural language processing to digitize students’ written work, identify errors, and classify them by type. This allows teachers to provide targeted interventions and better manage classroom data. By automating routine tasks, OPA aims to save time for educators and improve student literacy. The study demonstrates the potential of AI to transform educational practices, particularly in resource-limited environments, and addresses the lack of AI tools in Portuguese language education.